KESEHARIAN ISTERI NELAYAN: STUDI ANTROPOLOGI TENTANG POLA NAFKAH PADA KOMUNITAS NELAYAN DI NAGARI TIKU SELATAN, KECAMATAN TANJUNG MUTIARA, KABUPATEN AGAM - Hendrawati - - (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2014)
This article is the result of research on the role of women fishing households living systems. The contribution of women in household income earned through productive activities that they do. These activities, among them, is the involvement of women in the marketing of the fisheries and involvement in the processing of the fisheries. Small industries in rural apparently has a role in increasing the contribution of women in their household income.  Livelihood strategies undertaken by poor fishermen households consisting of economic strategies and social strategies. Economic strategy by performing a double living patterns, utilization of household labor and migration. While social strategy is done by utilizing the existing ties of kinship. Traditional welfare institutions also have an important role to poor households in meeting their needs. Social capital has an important role in the livelihood strategies of poor households in Nagari Tiku Selatan